Analisis Tanda dan Makna pada Desain Logo Sanggar Tari Puspitasari - Rina Nurfitri (Program Studi Desain Komunikasi Visual, Fakultas Sains dan Teknologi, Universitas Ma Chung, 2021)
The logo has an aesthetic value in accordance with the art elements contained in the design. The uniqueness of the Puspitasari logo is related to the characteristics of the studio. The logo becomes a determinant or even as a symbol of the existence of a training place. The logo used in Puspitasari consists of a logotype and a logogram. This can be seen in the use of lettering techniques combined with image elements. Pupitasari's logo is dominated by writing because it contains words, letters, slogans. From the classification of shapes contained in the logo, in terms of construction, Puspitasari is included in the picture mark as well as the lettermark. These signs complement each other with the combination of the use of logograms and logotypes that can be said to represent the identity of the Puspitasari dance studio. The characteristic displayed on the logo represents the shape of the dancer's body and the flower petal symbol represents the name of the dance studio, namely the Puspitasari dance studio.